Analisis Du Pont System untuk Menilai Kinerja Keuangan PT ABC, Tbk Periode 2019-2023 - Nur Anisah; Dewi Fadila; Hendra Sastrawinata (Jurnal Bisnis Kreatif dan Inovatif, 2025)
This study aims to analyze the financial performance of PT ABC Tbk during the period 2019–2023 using the Du Pont System as the primary analytical tool. The Du Pont System is widely recognized as a comprehensive method to evaluate a company’s overall performance by breaking down profitability into several key components: net profit margin, total asset turnover, return on investment (ROI), equity multiplier, and return on equity (ROE). The research employs a descriptive quantitative approach, with data sourced from secondary materials in the form of official financial statements published by the Indonesia Stock Exchange (IDX). A purposive sampling technique was applied to ensure the relevance and accuracy of the data analyzed. The findings reveal that the company’s financial performance throughout the five-year observation period has been less than optimal. Each of the main components of the Du Pont System showed average ratios that fell below the industry benchmark, indicating structural weaknesses in both profitability and efficiency. Specifically, the net profit margin and total asset turnover were constrained by high operational costs, while ROI and ROE were further pressured by volatility in foreign exchange rates. These inefficiencies highlight the vulnerability of the company’s financial structure to both internal management challenges and external macroeconomic factors. Based on the results, the study provides several strategic recommendations to improve financial performance. First, optimization of cost management is necessary to reduce operational inefficiencies that directly affect profit margins. Second, the implementation of foreign exchange risk mitigation strategies, such as hedging, is suggested to minimize the negative impacts of currency fluctuations. Finally, to strengthen revenue growth, the company is encouraged to adopt and expand digital marketing initiatives as a means of improving sales performance and market penetration. Overall, this study emphasizes the importance of integrating financial control with strategic innovation to ensure long-term sustainability and competitiveness in the pharmaceutical industry.